Impact resistance of BIPV systems: New testing procedure for performance assessment of multifunctional products. Issue 1 (15th December 2022) - Bonomo, Pierluigi; Parolini, Fabio; Corti, Paolo; Frontini, Francesco; Bellenda, Giovanni; Caccivio, Mauro
Abstract: Building integrated photovoltaics (BIPV) is progressively achieving an advanced level of technical maturity and considerable market penetration. In the last kilometre for considerable market implementation, major challenges are today mostly related to improving cost‐effectiveness and product reliability. BIPV multifunctional products are still framed in complex and sometimes unclear qualification processes, in the grey area between electrotechnical and construction sectors, impacting commercialization and users' confidence. The EN 50583 part 1 and part 2 standards today represent the main regulatory framework in Europe for BIPV. However, acts in force for product certification, in the construction and electrical sectors, in most national and local contexts are not yet harmonized for BIPV and imply wide margins of interpretation. The product's qualification in the EU is therefore based on electrical standards for photovoltaics modules or, on the other hand, on standards for construction products. To overcome some of these barriers and challenges, the authors propose a newly developed procedure for testing the impact resistance of BIPV products, introducing a performance‐based approach with the goal of combining building and electrical‐related limit states and responding to the need for a harmonized assessment to ensure the product's safety in use. The methodology and preliminary findings resulting from the application of real test cases, taking also into account the effect of temperature, are presented and analysed. As a result, it is envisaged that the implementation will help operators and prospective normative upgrades, ensuring more outstanding product quality for BIPV's market and driving towards a drop in life cycle costs. Abstract : Test set up of hard body impact.